Teachers’ self-efficacy is related to their nutrition teaching methods: Self-efficacy and nutrition teaching methods - Unusan, Nurhan; Yalcin, Hatice (Progress in Nutrition, 2020)
Background: Teacher-led nutrition education is a practical method for informing children about healthy eating at an early age. Commonly reported teacher barriers include self-efficacy and use of teaching methods.Objective: This study is the first to evaluate preschool teachers’ self-efficacy in teaching nutrition and their preferred teaching methods.Material and Method: Researchers recruited preschool teachers from 133 preschools in Konya. At the baseline, teachers were asked to provide demographic information, including their age, sex, level of education, teaching experience, previous involvement in teaching nutrition and resources used to plan nutrition lessons. The completed survey data were entered into SPSS 24. The data were analysed using descriptive statistical methods, and each question was analysed for frequencies. Kendall’s Tau-b was used throughout the analysis to determine the relationships among the variables (self-efficacy and teaching methods).Results: All of the teachers were female. The baseline score for self-efficacy was relatively high, with an average of 74±65.6. Teachers who demonstrated decreases in self-efficacy were those who reported previous experience teaching nutrition, and those who showed increases in self-efficacy were those who reported no previous experience teaching nutrition. Kendall’s Tau-b showed a statistically significant relationship between self-efficacy and teaching method and indicated a statistically significant relationship between the belief that teachers are doing a good job regarding the health of students and role playing, 0.194 (p